Pengaruh Retribusi Daerah dan Pajak Daerah Terhadap Pendapatan Asli Daerah Provinsi Bali dan Nusa Tenggara Barat Periode 2019-2021 - Taufiqurrahman, Dimas; Trisnaningsih, Sri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of the level of effectiveness and contribution of the realization of local retribution and local taxes on local revenue in the Cities / Regencies of Bali and West Nusa Tenggara Provinces in the 2019-2021 period. The research method used is descriptive with a quantitative approach. The data analysis technique was carried out by effectiveness analysis, contribution analysis, and panel data regression analysis using Eviews SV 12. The results showed that the level of effectiveness and contribution of local levies in cities / districts in Bali and West Nusa Tenggara Provinces for the 2019-2021 period was less effective and very insufficient, which meant that it had no effect on local revenue. Meanwhile, the level of effectiveness and contribution of local taxes in cities / regencies in Bali and West Nusa Tenggara provinces for the 2019-2021 period is effective and moderate, which means it has an effect on local revenue.